Biophysical and Characterizations of Silver Nanoparticles used as Salmonella typhi Detector - Ahmed, Hala Moustafa (International Journal of Applied Sciences and Biotechnology, 2014)
The present study mainly focuses of combined action of Nepali hog plum as well as citrate synthesized silver nanoparticles (AgNPs) and Amikacin, as an antibiotic. The synergistic actions of citrate stabilized silver nanoparticles (AgNPs with chem) were compared with that of Nepali hog plum Choerospondia saxillaris (Lapsi) synthesized silver nanoparticles (AgNPs with plant), together with action of antibiotic onselected bacterial strains of Salmonella typhi. The synthesized AgNPs were characterized through UV-Vis spectroscopy, Transmission electronmicroscopy and X-ray diffraction technique. The size of the synthesized silver nanoparticles was measured by Transmission Electron Microscope (TEM) and X-ray diffraction (XRD). DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11127 Int J Appl Sci Biotechnol, Vol. 2(4): 510-515